Pengembangan Blog Pembelajaran Fun Chemistry Pada Materi Sistem Periodik Unsur Kelas X SMA - Sri Sulistyaningsih N.D Tiring; Klaudius Ware; Ana Pratiwi (Jurnal Ilmiah Wahana Pendidikan, 2022)
This study aims to determine the stage of development of a chemistry learning blog on the periodic table element material for class X SMA and the feasibility level of a chemistry learning blog on the periodic table element material for class X SMA. The research was conducted at SMASK Sint Gabriel Maumere and SMA Negeri 2 Maumere. This type of research is in the form of research and development by following the Borg and Gall development model. The instruments used in this study were validation sheets and a feasibility questionnaire. The subjects in this study, namely in the initial field trial with 10 students in class X MIA and involving two chemistry teachers, further trials with 20 students in class X MIA and involving two chemistry teachers, and the final field trial with 40 students in class X MIA and involving two chemistry teachers. The validation data analysis technique and the feasibility questionnaire analysis respectively used the validation percentage and the Ernawati & Totok formula category based on the Likert scale.